2019
DOI: 10.3390/w11010092
|View full text |Cite
|
Sign up to set email alerts
|

The Multi-Scale Temporal Variability of Extreme Precipitation in the Source Region of the Yellow River

Abstract: Changes in extreme precipitation are critical to assess the potential impacts of climate change on human and natural systems. This paper provides a comprehensive investigation on the multi-scale temporal variability of extreme precipitation in the Source Region of the Yellow River (SRYR). The statistical analysis explores multi-scale extreme precipitation variability ranging from short to long term, including seasonal, annual, and inter-annual variations at different locations in the SRYR. The results suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…A previous study indicated that the summer monsoon strongly influences the middle and lower reaches of the Yangtze River, thus leading to abundant precipitation and making the area humid [12]. A contour image of monthly precipitation during 1967-2018 shows heavy precipitation was concentrated between April and September with June as the peak value ( Figure 5), which is similar with the phenomenon in the Yellow River [13] and Dongting Lake located at the middle of the Yangtze River [4]. Ye et al [14] also reported that a large amount of surface flow was produced by heavy precipitation during wet season, which caused the rise of water level in Poyang Lake (located opposite the Huayang Lakes) adjacent to the Yangtze River.…”
Section: Relationship Between Precipitation and Water Levelsupporting
confidence: 68%
“…A previous study indicated that the summer monsoon strongly influences the middle and lower reaches of the Yangtze River, thus leading to abundant precipitation and making the area humid [12]. A contour image of monthly precipitation during 1967-2018 shows heavy precipitation was concentrated between April and September with June as the peak value ( Figure 5), which is similar with the phenomenon in the Yellow River [13] and Dongting Lake located at the middle of the Yangtze River [4]. Ye et al [14] also reported that a large amount of surface flow was produced by heavy precipitation during wet season, which caused the rise of water level in Poyang Lake (located opposite the Huayang Lakes) adjacent to the Yangtze River.…”
Section: Relationship Between Precipitation and Water Levelsupporting
confidence: 68%
“…Spatially, precipitation increased significantly in the northwestern SAYR (Tian et al, 2015). In summary, the climate in the SAYR has exhibited a warming-wetting trend and the extreme weather events have become more frequent (Han et al, 2018;Jiang et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
“…Particularly, in the 21st century, the climate wetting in the SRYR accelerated [41][42][43]. The average precipitation in 2001-2019 increased by 29.8 mm compared with that in 1961-2000 [39,44,45].…”
Section: Flood Disastermentioning
confidence: 99%